Woven composites - Aliabadi, M. H. (Imperial College Press, 2015)
This unique volume presents the latest developments in the field of advanced woven and braided textile composites, with particular emphasis on computational approaches (finite elements, meshfree). Advanced textile composites such as woven, braided, knitted and stitched fabrics are increasingly being used as structural materials in industrial applications due to their efficiency at reinforcing more directions within a single layer and their ability to conform to surfaces with complex curvatures. Furthermore, textile composites provide improved impact resistance, exceptional thermal, fatigue and corrosion resistance, as well as being easier and cheaper to handle and fabricate compared to UD composites. Topics covered in this book include: 2D and 3D plain, twill, satin woven and braided composites, micro-level and macro-level modelling, failure mechanisms, theoretical studies on cryogenic crack behaviour and the specific deformation modes of textile reinforcements, which include the kinematic and hypoelastic models. This book will be particularly relevant to professional engineers, graduate students and researchers interested in composite materials.
Keywords: Fibrous composites.; Reinforced plastics.; Textile fabrics.; elektronické knihy; electronic books